Aquafilling Filler for Buttock Augmentation Cause Severe Long-Term Complications: A Case Report - Kristiansen, Camilla Soendergaard; Lang, Christian Lyngsaa; Haerskjold, Ann; Zachariae, Claus; Klit, Anders (Indian Journal of Plastic Surgery, 2025)
Filler injections for buttock augmentation are becoming more popular as a cosmetic procedure, which leads to an expected increase in the number of complications emphasizing the importance of reporting cases with both well-known, severe, and previously undiscovered complications, as well as their possible treatment strategies.We present an 18-year-old woman who suffered severe long-term complications following Aquafilling injections for buttock augmentation, including filler migration, infection leading to septic shock, and nonparathyroid hypercalcemia, which has the potential to cause renal insufficiency. To date, we have not found any reports describing the association between nonparathyroid hypercalcemia and Aquafilling. Additionally, we outline a treatment regimen involving a minimally invasive approach, which includes daily irrigation, manual compression, and passive evacuation. At follow-up, the patient returned to her everyday life with no lasting sequelae, except for a solid mass medially on the right thigh.
Keywords: filler injections; Aquafilling; complications